Sr2Y8(SiO4)6O2:Bi3+/Eu3+: a single-component white-emitting phosphor via energy transfer for UV w-LEDs. Issue 38 (11th September 2015) - Li, Kai; Fan, Jian; Shang, Mengmeng; Lian, Hongzhou; Lin, Jun
Abstract : A series of tunable blue-green to white phosphors, Sr2 Y8 (SiO4 )6 O2 :Bi 3+, Eu 3+ phosphors, prepared via a Pechini-type sol–gel method have been investigated. Abstract : A series of Bi 3+, Eu 3+ -doped Sr2 Y8 (SiO4 )6 O2 (SYSO) phosphors were synthesized by the Pechini-type sol–gel route. XRD patterns, Rietveld refinement, FT-IR spectra, photoluminescence spectra (PL), fluorescence decay time, and quantum yields (QYs) were utilized to characterize the as-prepared samples. Intense blue-green emission due to the 3 P1 → 1 S0 transition of Bi 3+ ions is produced under UV excitation in Bi 3+ singly doped SYSO samples. Spectral analysis illustrates that two kinds of Bi 3+ ions are generated by occupying the two kinds of sites (4f and 6h) available for Y in SYSO, denoted as Bi 3+ (1) and Bi 3+ (2), corresponding to the two main emission bands at around 413 and 493 nm, respectively. A wide spectral overlap between Bi 3+ emission and Eu 3+ excitation spectra results in the energy transfer from Bi 3+ to Eu 3+ . This has been demonstrated via the excitation spectra monitored at Bi 3+ and Eu 3+ emission bands, and the PL emission spectra and decay time of Bi 3+ in SYSO:Bi 3+, Eu 3+ phosphors. The energy transfer mechanism is determined to be dipole–quadrupole interaction. The critical distance of energy transfer from Bi 3+ to Eu 3+ ions is calculated to be 12.78 Å based on the concentration quenching method, which is in good agreement with that of the spectral overlap route (10.03–13.37 Å). Moreover, the QYs, CIE chromaticity and thermal quenching properties have also been investigated. White emission color can be realized with the CIE coordinates (0.325, 0.311) and QY 52% for SYSO:0.08Bi 3+, 0.48Eu 3+ . The above results suggest that SYSO:Bi 3+, Eu 3+ can be a potential single-component white-emitting phosphor for UV w-LEDs.